1991
DOI: 10.1111/j.1349-7006.1991.tb01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Restriction Fragment Length Polymorphism of the Human Cytochrome P450IIE1 Gene and Susceptibility to Lung Cancer

Abstract: Cytochrome P450IIE1 (P450IIE1) is involved in metabolic activation of carcinogenic nitrosamines, aniline and benzene. We detected a restriction fragment length polymorphism of the human P450IIE1 gene with the restriction endonuclease Oral. The population was thus divided into three genotypes, namely, heterozygotes (CD) and two forms of homozygotes (CC and DD). The distribution of these genotypes among lung cancer patients differed front that among controls with statistical significance of P< 0.05 (x2=7.01 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(90 citation statements)
references
References 10 publications
0
90
0
Order By: Relevance
“…However, there are also indications of genetic predisposition to lung cancer (reviewed by Sellers, 1996;Lichtenstein et al, 2000) with some evidence that smoking-related cases are associated with polymorphisms in CYP2 genes involved in the metabolic activation of procarcinogens in cigarette smoke (Uematsu et al, 1991). If differences in carcinogen metabolism underlie susceptibility to lung cancer, these differences would not be detected by the G 2 assay.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also indications of genetic predisposition to lung cancer (reviewed by Sellers, 1996;Lichtenstein et al, 2000) with some evidence that smoking-related cases are associated with polymorphisms in CYP2 genes involved in the metabolic activation of procarcinogens in cigarette smoke (Uematsu et al, 1991). If differences in carcinogen metabolism underlie susceptibility to lung cancer, these differences would not be detected by the G 2 assay.…”
Section: Discussionmentioning
confidence: 99%
“…44) Individuals with the variant Rsa1 allele have a lower basal CYP2E1 activity. Overrepresentation of the variant CYP2E1 Rsa1 and Dra1 alleles was reported in Japanese 13,14,45) and a lower frequency of the Dra1 variant allele was found in lung cancer patients than in controls. A study in Japanese also found a 13.5% allele frequency for the rare CYP2E1 Pst1 site among all lung cancer patients and a significant association between the variant CYP2E1 Pst1 allele and lung AC.…”
Section: Discussionmentioning
confidence: 99%
“…Common homozygote (TT), heterozygote (TA), and rare homozygote (AA) genotypes of CYP2E1*6 were named DD, DC, and CC, respectively. CYP2E1*6 doesn't affect gene transcription, but it is likely to affect CYP2E1 catalytic activity (Uematsu et al, 1991). CYP2E1*7B (rs6413420; G-71T) was also found in the promoter region of the gene.…”
mentioning
confidence: 94%